NEUROBIOCHEMICAL DISORDERS AND THEIR ASSOCIATION WITH DISEASES (Academicia Globe: Inderscience Research, 2025)
This article analyzes the disorders of neurobiochemical processes and their relationship with various neurological and psychiatric diseases. It is emphasized that imbalances in the level of neurotransmitters, changes in the activity of ion channels, and disorders of protein metabolism play an important role in the development of nervous system diseases. The participation of neurobiochemical mechanisms in the pathogenesis of diseases such as depression, schizophrenia, Alzheimer's, Parkinson's, and epilepsy is reviewed based on scientific literature. The importance of neurobiochemical markers in diagnosis and treatment is also highlighted.